Oligodynamic Action of Silver, Copper and Brass on Enteric Bacteria Isolated from Water of Kathmandu Valley - Shrestha, Rajani; Joshi, Dev Raj; Gopali, Jyotsna; Piya, Sujan (Nepal Journal of Science and Technology, 2010)
Traditionally certain metal pots are used to store drinking water in order to ensure safety. A study was conducted with the aim of evaluating the effect of oligodynamic metals such as copper, silver and brass against enteric gram negative drinking water isolates such as Salmonella paratyphi, Shigella spp., E. coli (MDR), E. coli, Vibrio cholerae and Klebsiella during September 2007 to January 2008. The test was carried out by preparing broth of the respective microorganisms followed with contaminating autoclaved distilled water with 1% (by volume) of the prepared broth culture and incubating the contaminated water in the respective metal pots up to 48 h (holding time). Reduction in the microbial load was assessed by pour plating the water content in the metal pots on Nutrient agar medium in every 0, 4th, 8th, 12th, 24th and 48th h of incubation (holding time). Among three test pots, copper pot showed the maximum bactericidal action compared to silver and brass pots towards most of the enteric gram negative bacterial isolates of water. Complete inhibition of tested organism was recorded within 4 to 48 hours of holding time. This study suggested the promotion of use of water pots made of oligodynamic metals such as silver and copper, and alloy such as brass to control the gram negative enteric pathogens in drinking water. Key words: Oligodynamic action; Heavy metals; Enteric bacteria DOI: 10.3126/njst.v10i0.2959 Nepal Journal of Science and Technology Vol. 10, 2009 Page: 189-193